PENERAPAN SISTEM INFORMASI TUMBUH KEMBANG BALITA (SITUMBANG) DI POSYANDU NGADI ASIH KADIPIRO BANJARSARI SURAKARTA - Darah Ifalahma; Nurhayati Nurhayati; Ana Yuliana; Novia Kartika Hayu Asri (Jurnal Abdimas Bina Bangsa, 2023)
Posyandu Ngadi Asih is one of the Posyandu for Toddlers in the Kadipiro Village area, Banjarsari District, Surakarta City and is included in the Targeted Area of ​​Gambirsari Health Center, Surakarta. Posyandu Ngadi Asih has a cadre of 15 people and has implemented 5 posyandu service desks but is not yet optimal. The problems found at the Ngadi Asih Posyandu were that recap records of growth and development examination data were often lost, notes were tucked away and not neat, some data was not written down, some data was missed and incomplete. The root of the problem is that the recording of growth and development inspection results is still manual (paper based) by filling out the register book. Apart from that, it cannot be concluded whether the condition of the child's growth and development is normal or requires intervention, and an examination of the child's development has not been carried out due to the limited capabilities of the cadres. The solution offered by this program is the implementation of the Toddler Growth and Development Information System (Situmbang) and training in the use of the SDIDTK (Early Growth and Development Intervention Detection Stimulation) instrument. The implementation method with 6 (six) main activity stages, namely preparation, apperception, training, mentoring, evaluation and termination. The results of the program for implementing the Toddler Growth and Development Information System (Situmbang) at the Ngadi Asih Surakarta Posyandu have gone well. There is an increase in the skills of cadres after the activity is carried out, although not in its entirety. Some cadres still need assistance from skilled cadres. The Toddler Growth and Development Information System (Situmbang) is ready to be implemented at the Ngadi Asih Posyandu. The cadres are committed to implementing and implementing the results of this program in every posyandu activity and when providing support for Toddler Family Development